Frequency of Serum Electrolytes in Children Suffering from Acute Gastroenteritis Aged 6 Months to 3 Years Admitted to MTI DHQ Hospital Dera Ismail Khan : Electrolyte Imbalance in Gastroenteritis - Khan, Oushna; Burki, Farman Ullah; Khan, Imran; Yahya, Alina; Khan, Ayesha (Pakistan Journal of Health Sciences, 2025)
Acute Gastroenteritis (AGE) is a major contributor to morbidity, dehydration, and hospitalizations among young children in low-resource settings. Electrolyte disturbances are common complications that may worsen disease severity and outcomes. Objective: To evaluate the clinical presentation and laboratory findings, particularly serum electrolyte levels, in children aged 6 months to 3 years diagnosed with AGE, and to assess their association with dehydration severity. Methods: A descriptive-analytical cross-sectional study was conducted at MTI DHQ Hospital, Dera Ismail Khan, involving 110 children with AGE. Data on demographics, clinical features, hydration status, and laboratory results (including serum electrolytes) were recorded. Statistical analysis was performed using SPSS Version 25.0. Chi-square, ANOVA, Kruskal-Wallis, and Tukey’s HSD post-hoc tests were applied. A p-value ≤ 0.05 was considered statistically significant. Results: Vomiting (76.4%) and fever (64.5%) were the most frequent clinical features. Moderate dehydration was most common. Significant differences (p ≤ 0.05) in electrolyte levels were observed across dehydration groups: sodium, potassium, chloride, urea, and creatinine levels were elevated in severe cases, while bicarbonate and magnesium were lower. No significant associations were found between dehydration severity and demographic or most clinical variables. Conclusions: Electrolyte abnormalities were significantly associated with dehydration severity in children with AGE, emphasizing the need for routine electrolyte monitoring and individualized fluid management, especially in moderate to severe cases. These findings support improved diagnostic protocols and targeted treatment strategies in paediatric gastroenteritis care.